Zoonois, dan Gelombang Pandemi COVID-19 - Parwanto, ML Edy (Fakultas Kedokteran Universitas Trisakti, 2023)
Zoonoses are a group of diseases that can be transmitted to humans by non-human vertebrate animals. The source of zoonoses is a large number of domesticated and wild animals. Causes of zoonoses include viruses, bacteria, parasites, and fungi. Initially, it was stated that COVID-19 was caused by the novel coronavirus 2019 (nCoV-2019), then WHO stated that the name that caused COVID-19 was severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Although COVID-19 caused by SARS-CoV-2 has been classified as a zoonotic disease, no animal reservoir has been found, so the classification is premature. The proposed term for COVID-19 is classified as an “emerging infectious disease (EID) of probable animal origin.” Transmission of COVID-19 is exclusively in the form of human-human transmission, so it is not in accordance with the zoonotic definition of WHO.